PENERAPAN WASPAS DALAM MENDUKUNG KEPUTUSAN PENERIMA BEASISWA MAHASISWA BERPRESTASI - Pagan, Darmandra Mirza; Syahrizal, Muhammad (TIN: Terapan Informatika Nusantara, 2020)
In processing data on high-achieving student scholarships in the Office of Personnel and Human Resources Development (KKPSDM) in general, they still use a manual system, namely there is no computerization in determining the recipients of outstanding student scholarships so that there are many problems that occur in this system. The problem that arises is the lack of proper distribution of scholarship recipients and high achieving students, for example, students who are not actually eligible for scholarships but get scholarships, on the other hand, students who are entitled to get good scholarships are outstanding scholarships or underprivileged scholarships but do not get scholarships. Such problems arise because of the lack of careful scholarship selectors in selecting scholarship recipients because the scholarship selectors themselves are in the Human Resources and Human Resources Development Office (KKPSDM) so there is insufficient time available to select scholarship recipients, so there is an error in determining scholarship recipients precisely due to lack of careful selection